Implementation of the Electronic Attendance System as an Instrument for Enforcing Civil Servant Discipline Based on Government Regulation Number 94 of 2021 - Muhamad Abil Rachman; Andari Yurikosari (CV Edujavare Publishing, 2026)
The implementation of an electronic attendance system is part of the digital transformation in Civil Service management aimed at improving Civil Servant (PNS) discipline. This study aims to analyze the implementation of the electronic attendance system as an instrument for enforcing civil servant discipline based on Government Regulation Number 94 of 2021 at the Sukabumi Class I Non-TPI Immigration Office and identify efforts made to overcome obstacles to its implementation. This study uses a normative legal research method with a statute approach, supported by literature studies and interviews as supplementary data. The results show that the implementation of the electronic attendance system through the STAR ASN application has supported improved employee discipline, particularly in compliance with working hours, transparency of attendance data, and effective supervision. However, its implementation still faces obstacles such as internet network disruptions, application system constraints, and limited supporting facilities. To address these issues, the Sukabumi Class I Non-TPI Immigration Office coordinates with application administrators, implements an attendance verification mechanism when system disruptions occur, and strengthens internal guidance and supervision. Thus, the electronic attendance system has become an effective instrument in supporting the enforcement of civil servant discipline in accordance with the provisions of Government Regulation Number 94 of 2021.